2021
DOI: 10.3390/w13212944
|View full text |Cite
|
Sign up to set email alerts
|

Study on Adsorption of As(III) by a New Bio-Material from Chitin Pyrolysis

Abstract: Chitin-char is obtained from fast pyrolysis of chitin. To obtain the maximum surface area, chitin-char is treated by nitric acid. Then, a kind of new arsenic removal bio-material is prepared by loading Ca(OH)2 on the char (called Ca(OH)2-char). IR spectroscopy before and after char treatment reveal at least three distinct patterns of peak changes. An adsorption study is performed at different doses, pHs, and coexisting ions in the batch mode. The adsorption kinetics follows two first-order equations. Kinetic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Besides, many researchers have found that the presence of Ca 2+ promotes the removal of arsenic through the formation of Ca‐As sediments (Zama et al, 2022). The mechanism of arsenic removal by lime (CaO) and hydrated lime (Ca (OH) 2 ) has been proved to be through the precipitation of different types of calcium arsenate salts (Yang et al, 2021; Zama et al, 2022). The main components of the calcined oyster shell are CaCO 3 and CaO, which may form calcium arsenate precipitation in the process of As(III) removal, thus improving the As(III) adsorption efficiency of FMBO/OS (Mollah et al, 2004; Wang & Zhu, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, many researchers have found that the presence of Ca 2+ promotes the removal of arsenic through the formation of Ca‐As sediments (Zama et al, 2022). The mechanism of arsenic removal by lime (CaO) and hydrated lime (Ca (OH) 2 ) has been proved to be through the precipitation of different types of calcium arsenate salts (Yang et al, 2021; Zama et al, 2022). The main components of the calcined oyster shell are CaCO 3 and CaO, which may form calcium arsenate precipitation in the process of As(III) removal, thus improving the As(III) adsorption efficiency of FMBO/OS (Mollah et al, 2004; Wang & Zhu, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, many researchers have found that the presence of Ca 2+ promotes the removal of arsenic through the formation of Ca-As sediments (Zama et al, 2022). The mechanism of arsenic removal by lime (CaO) and hydrated lime (Ca (OH) 2 ) has been proved to be through the precipitation of different types of calcium arsenate salts (Yang et al, 2021;Zama et al, 2022) and CaO, which may form calcium arsenate precipitation in the process of As(III) removal, thus improving the As(III) adsorption efficiency of FMBO/OS (Mollah et al, 2004;Wang & Zhu, 2019). The FMBO/OS after As(III) adsorption was analyzed by XRD, as shown in Figure 7, which confirmed that Ca-As sediments, CaHAsO 4 Á3H 2 O (d = 4.96, 2.95, 2.63, and 2.51 Å), Ca(H 2 AsO 4 ) 2 (d = 3.04, 1.79 and 1.48 Å), and CaAs 2 O 6 (d = 2.94 and 2.96 Å) had formed (Mollah et al, 2004).…”
Section: Mechanism Of Removal Of As(iii) By Fmbo/osmentioning
confidence: 99%
“…and chemical (corrosion treatment, etc.) methods [16][17][18][19]. Xiang et al [20][21][22] revealed that the maximum adsorption capacity of biochar for fluvoxamine was positively correlated with specific surface area, which indicated that the adsorption capacity had a great relationship with specific surface area.…”
Section: Introductionmentioning
confidence: 99%